2017
DOI: 10.1177/0260106017700436
|View full text |Cite
|
Sign up to set email alerts
|

Six weeks of β-alanine supplementation did not enhance repeated-sprint ability or technical performances in young elite basketball players

Abstract: Supplementation with β-alanine plays an important role as a precursor of carnosine, the most effective intramuscular buffer, and has been seen as a potential ergogenic aid, especially for high-intensity modalities such as basketball. Thus, the aim of the present study was to investigate the effects of 6 weeks of β-alanine supplementation on repeated sprint ability (RSA) and technical performances in young elite Brazilian basketball players. In total, 27 young basketball players (17±1 years) were randomized int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
2
14
1
Order By: Relevance
“…Short-term BA supplementation (3 weeks) was unable to attenuate this training-associated decline in YoYo IR1 performance. The lack of an effect shown here is line with previous research showing no changes in YoYo IR1 in young elite male basketball players with BA supplementation (20), although BA did improve YoYo IR2 (19) in amateur male footballers. The YoYo IR2 is initiated at a higher intensity than the YoYo IR1, with a higher contribution from anaerobic glycolytic pathways increasing the contribution of buffering capacity to performance (9), making it more susceptible to improvements with BA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Short-term BA supplementation (3 weeks) was unable to attenuate this training-associated decline in YoYo IR1 performance. The lack of an effect shown here is line with previous research showing no changes in YoYo IR1 in young elite male basketball players with BA supplementation (20), although BA did improve YoYo IR2 (19) in amateur male footballers. The YoYo IR2 is initiated at a higher intensity than the YoYo IR1, with a higher contribution from anaerobic glycolytic pathways increasing the contribution of buffering capacity to performance (9), making it more susceptible to improvements with BA.…”
Section: Discussionsupporting
confidence: 91%
“…It is considered an effective ergogenic aid by the International Olympic Committee (18), although the effects of beta-alanine on football-specific protocols is unclear and contradictory. Beta-alanine has previously improved YoYo IR2 performance in amateur male footballers throughout a competitive season (19), although YoYo IR1 was not improved in young elite male basketball players (20). Evidence to support beta-alanine supplementation during shorter-duration repeated sprints is distinctly lacking (21-23) although supplementation alongside plyometric training did lead to greater improvements in RAST than training alone in female soccer players (11).…”
Section: Introductionmentioning
confidence: 98%
“…An RSA protocol was used to simulate high intensity exercise (all-out sprints) (Milioni, Redkva, Barbieri, & Zagatto, 2017;Padulo, Laffaye et al, 2015). The test consisted of ten 30 m sprints with two 180°changes of direction (10 m + 10 m + 10 m), interspaced by 30 s of passive recovery between the sprints (Padulo, Laffaye et al, 2015;Zagatto et al, 2017) and with an exercise-to-rest ratio of 1:5 (Ruscello et al, 2013) (test-retest Intraclass correlation > 0.90) (Padulo, Laffaye et al, 2015).…”
Section: Repeated Sprint Ability Testmentioning
confidence: 99%
“…Despite the potential to increase muscle buffering capacity, the effect of ␤-alanine supplementation on RSA performance and the likely mechanisms involved are unexplored. Sweeney et al (43), Ducker et al (13), and Milioni et al (33) showed no ergogenic effect of ␤-alanine supplementation on RSA performed in running (nonmotorized treadmill, running track, and sprints with change of direction), while Brisola et al (8) and Claus et al (10) observed discrete improvement on RSA performed in swimming by professional and young water polo players.…”
Section: Introductionmentioning
confidence: 99%